Diffuse Enlargement of the Thyroid Gland as a Result of the Impact of Adverse Factors on the Pituitary-thyroid Cystem of Children (Bangladesh Journal of Medical Science, 2024)
The problem of diffuse goiter has attracted the attention of many researchers in recent years. The main reason for the formation of endemic goiter is iodine deficiency in the environment. Epidemiological studies conducted in recent years have shown that almost all regions of Kazakhstan are regions of endemic goiter with natural iodine deficiency. Some of them are characterized by an increase in the severity of endemic goiter. The reasons contributing to the progression of goiter endemicity are the cessation of iodine prophylaxis, the deterioration of the environmental situation and the social situation of a significant part of the population. The purpose of this work was to study the features of thyroid status in children with diffuse goiter. Material and methods There were 38 children under our supervision, 20 (main group) had diffuse (endemic) goiter (5 boys and 15 girls), 18 children (control group) - 5 boys and 13 girls, children in the control group were considered healthy. Results As a result of comparing indicators of the functional state of the pituitary-thyroid system in patients with diffuse goiter, a relatively increased level of thyroid-stimulating hormone is noted, which indicates the negative impact of diffuse goiter on the thyroid status of children. Conclusions As a result of the manifestation of diffuse goiter in children, metabolic disorders of the pituitary-thyroid system occur. Signs of thyroid deficiency are most often observed in children living in iodine-deficient areas.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1213-1218